Preparation and Evaluation of 6-Gingerol Derivatives as Novel Antioxidants and Antiplatelet Agents - Sara H. H. Ahmed; Tímea Gonda; Orinamhe G. Agbadua; Gábor Girst; Róbert Berkecz; Norbert Kúsz; Meng-Chun Tsai; Chin-Chung Wu; György T. Balogh; Attila Hunyadi (MDPI AG, 2023)
Ginger (Zingiber officinale) is widely used as a spice and a traditional medicine. Many bioactivities have been reported for its extracts and the isolated compounds, including cardiovascular protective effects. Different pathways were suggested to contribute to these effects, like the inhibition of platelet aggregation. In this study, we synthesised fourteen 6-gingerol derivatives, including eight new compounds, and studied their antiplatelet, COX-1 inhibitor, and antioxidant activities. In silico docking of selected compounds to h-COX-1 enzyme revealed favourable interactions. The investigated 6-gingerol derivatives were also characterised by in silico and experimental physicochemical and blood-brain barrier-related parameters for lead and preclinical candidate selection. 6-Shogaol (2) was identified as the best overall antiplatelet lead, along with compounds 3 and 11 and the new compound 17, which require formulation to optimize their water solubility. Compound 5 was identified as the most potent antioxidant that is also promising for use in the central nervous system (CNS).